(untitled) (Cardiovascular Journal, 2018)
Background: The Ankle-Brachial Index has been shown to be a good marker of systemic atherosclerosis and a powerful indicator of cardiovascular morbidity and mortality This study evaluated the relation of ABI with the angiographic severity of patient with coronary artery disease. Methods: This is a hospital based cross-sectional analytical study. 100 adult Bangladeshi patients who were admitted and underwent coronary angiography according to inclusion and exclusion criteria were the study population. All patient’s ABI were measured and coronary angiography were done. Patients were divided into two groups according to ABI. Group I with ABI >0.90 and group II with ABI <0.90. Results: In group I 65(82.2%) were men and 16(19.8%) were women. In group II 18(94.7%) patients were men and 1(5.3%) was women. Significant co-relation was found between low ABI and severity of CAD. Low ABI group showed more severe form of CAD with higher prevalence of triple vessel diseases, significant stenosis and more involvement of left main (LM) and left anterior descending(LAD)artery. Single vessel disease was found more with normal ABI. Hypertension, diabetes mellitus and Low ABI showed predictors of significant severe stenosis of coronary arteries. Conclusion: Low ankle brachial index is a predictor of the severity of coronary artery disease. So it could be incorporated in our day to day clinical cardiology practice as non-invasive, bedside test to assess and predict the severity of coronary artery disease. Cardiovasc. j. 2018; 10(2): 201-205